Moraxella lacunata Bacteremia and Sepsis Associated With Ecthyma Gangrenosum: A Case Report and Review of the Literature. Issue 3 (May 2017) - Walker, Durane K.; Altamimi, Sarah; Henneberry, Jean
Abstract : Abstract: We report a case of Moraxella lacunata bacteremia and sepsis associated with ecthyma gangrenosum in a patient with a hematologic malignancy and successful treatment with antimicrobial therapy. Ecthyma gangrenosum, although classically associated with Pseudomonas aeruginosa, can occur with any bacterial, viral, or fungal infection. In this case report, we review the literature on Moraxella lacunata infections and conclude that it should be considered as a viable contender as a cause of ecthyma gangrenosum in any immunocompromised patient who presents with skin lesions and gram-negative rod bacteremia. Abstract : Ecthyma gangrenosum is classically associated with Pseudomonas bacteremia but can occur with other Gram-negative bacilli. Moraxella lacunata, though considered to be of low virulence, can cause serious infections in the immunocompromised host including bacteremia, sepsis, and ecthyma gangrenosum even if patients are taking prophylactic antibiotics to which M. lacunata is known to be susceptible.